ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PETANI DALAM MENERAPKAN POLA USAHATANI TUMPANGSARI CABAI MERAH DENGAN CABAI RAWIT HIBRIDA DI DESA BOCEK KECAMATAN KARANGPLOSO KABUPATEN MALANG - Dewi Setyo Utari; Farida Syakir; Bambang Siswadi (Program Studi Agribisnis, 2019)
ABSTRACTThis research have to determine the factors that influence the decisions of farmers in implementing farming intercropping pattern of red chili with cayenne pepper hybrids. The method of determining the research location intentional (purpusive) with the consideration that the village Bocek is a center for chili production, and using stratified random sampling method in determining the number of samples farmers intercropped many as 35 people and farmers monoculture 20 people, and use logistics analysis to determine the factors that affect farmers' decisions applying the cropping pattern. And based on the results of this study indicate that significant factors that influence the decisions of farmers in applying intercropping farming patterns are influenced by age, land size, family members, income, and frequency of following conseling, while variables effect is eduction, capital and experience of farming.Keywords: Intercropping, Red Chili, Cayenne Pepper, Monoculture